GUIDELINES FOR INCREASE VOLUME AND EFFICIENCY OF USE OF INVESTMENT RESOURCES IN THE REGIONAL ECONOMY IN THE CONDITIONS OF WAR - BOIKO, Ruslan (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The research focuses on the issues of effective state investment policy, focused on increasing the volume of investment and making the use of investments more efficient. The purpose of the article is to substantiate the guidelines for increasing volumes and making the use of investment resources more efficient in the regional economy in war conditions. It was found that effective and adaptive to modern dynamic reality investment policy of the region should be aimed at minimizing risks and threats that form negative factors of the investment environment, and maximizing positive effects that ensure the attractiveness and safety of the region for investors. At the same time, taking into account the development potential of the region is critically important, because it allows defining a coherent and consistent strategy aimed at economic and social growth, strengthening the security and stability of the territories in the face of the latest challenges. This approach corresponds to the concept of impact investing. Strategic solutions are indicated, the practical approbation of which will improve the investment environment of the region. The possibilities of investment development of the region are shown, as well as its threats are identified, among which the need to overcome and eliminate such threats to the further development of investment processes in the region is emphasized. These are: the prolongation of the war and the aggravation of security challenges; demographic crisis, depopulation of territories, loss of human capital; tinization and withdrawal of capital from the country; high level of external migration activity of business; loss of basic components of innovative and technological potential; strengthening of structural and spatial disparities, sectoral and sectoral disintegration; socio-political uncertainty, preservation of institutional instability.